Expansion of human and animal sporotrichosis in Manaus, Amazonas State, Brazil - Rosiane Mendes Valente; João Victor de Melo Verçosa; Eduardo Rodrigues de Souza; Natalia Prata Gordiano; Layssa do Carmo Barroso; Sonia Maria da Silva Carvalho; Marla Jalene Alves; Fernanda Rodrigues Fonseca; Maria Eduarda Grisolia; Maria Edilene Martins de Almeida; Paula Taquita Serra; Luis Andre Morais Mariúba; et al. (Cadernos de Saúde Pública)
Abstract: Sporotrichosis is an emerging fungal infection that has been causing concern in Brazil since the late 1990s and is the most prevalent and globally distributed among implantation mycoses. In Brazil, the increase in sporotrichosis cases is strongly associated with infections in cats. This study aimed to identify the epidemiological profile and expansion of sporotrichosis in the city of Manaus, Amazonas State, Brazil, based on cases reported from 2020 to 2023. Secondary data from confirmed sporotrichosis cases during this period in Manaus were employed. Human data were extracted from the Brazilian Information System for Notificable Diseases, the Manaus Municipal Health Department, and the RedCap database of the Amazonas Health Surveillance Foundation - Registry of Positive Cases. The animal data were extracted from the spreadsheet of the Dr. Carlos Durand Zoonoses Control Center in Manaus. Data analysis was performed using the RStudio software for the spatial distribution of cases in the QGIS program, which was used to define the areas with the highest absolute number of cases. From August 2020 to December 2023, 4,301 sporotrichosis cases were confirmed, including 3,403 animal cases (of which 99.6% involved cats) and 898 human cases. From 2022 to 2023, the number of human cases doubled and animal cases quadrupled, with cases reported across all areas of Manaus. The expansion of sporotrichosis was observed over a two-year period for nearly the entire area of Manaus, with a significant increase in cases and an association between animal and human cases.